Integrating Sketch and speech inputs using spatial information - Lee, Bee Wah; Yeo, Alvin Wee (Universiti Malaysia Sarawak (UNIMAS), 2005)
Since the development of multimodal spatial query, the integration in determining the correct pair of multimodal input remains a problem in multimodal fusion. Although there exist integration technique that have been proposed to resolve this problem, they are limited to the interaction with predefined speech and sketch commands. Furthermore, they are only designed to resolve the spatial query with single speech input and single sketch input. Therefore, when it comes to the introduction of multiple speech and sketch input in a single query, all the existing integration techiques are unable to resolve it.